Synthesis and electrical properties of doped layered perovskites based on BaMInO4 (M = Y, Gd) - Nataliia Tarasova; Maxim Mashkovtsev; Maxim Domashenkov; Denis Khionin; Roman Bastrikov; Anzhelika Bedarkova (Chimica Techno Acta)
Perovskite or perovskite-related structural materials are widely studied for their many functional properties. They can be used as components of electrochemical devices such as solid oxide fuel cells and electrolyzers. Layered perovskites can also be considered as promising materials for use in these devices. In this paper, the possibility of heterovalent (acceptor and donor) and isovalent doping of La and In sublattices of layered perovskites BaYLaInO4 and BaGdLaInO4 was made for the first time. The structure and electrical properties of these oxides were studied. Electrical conductivity values increase in the series BaYInO4–BaLaInO4–BaGdInO4. However, the doping is an unsuitable strategy for improving the electrical properties of BaYInO4 and BaGdInO4 oxides. Further search for highly conductive materials with the layered perovskite structure can be aimed at materials with a different composition of the cation sublattice.